IS THIS A BITTI? A CHEMICAL ASSESSMENT OF THE PIGMENTS PRESENT IN “EL SEÑOR DE LA CAÍDA” - Arízaga Torres, Jhonathan (2023)
Bernardo Bitti is one of the most important figures in the history of Peruvian viceregal painting. However, there are few studies focused on the technical characterization of his work. In the church of San Pedro de Lima, there are three canvas paintings attributed to Bitti, as well as a panel painting, with the title “El Señor de la Caída”, which could also belong to this author, and which is the object of this investigation. This study was focused on the chemical analysis of the pigments that were used in this painting through portable X-ray fluorescence spectroscopy, optical microscopy, Raman microspectroscopy, and scanning electron microscopy to evaluate if it could belong to Bitti’s time. Even though some modern pigments were detected, they seem to come from later interventions. The pigments that were identified as belonging to the painting during this investigation were lead white, azurite (in some blue tones), vermilion (reds and flesh tones), lead-tin yellow and gypsum (ground layer). Additionally, based on the obtained results, it is proposed that ochres and earths may have been used in the brown tones and a red lake in the pink ones, but this must be confirmed by further analyses. Since all these pigments are in agreement with what was used in Bitti’s time, we cannot rule out the possibility that “El Señor de la Caída” may have also been painted by this artist. With this investigation we seek to contribute to the dissemination of the material technique used in Peruvian viceregal painting, as well as to the construction of a database for studies related to Bitti and other artists of his time.